Regeneration of injured skeletal muscle in heat shock transcription factor 1‐null mice. Issue 3 (29th August 2013) - Nishizawa, Sono; Koya, Tomoyuki; Ohno, Yoshitaka; Goto, Ayumi; Ikuita, Akihiro; Suzuki, Miho; Ohira, Tomotaka; Egawa, Tatsuro; Nakai, Akira; Sugiura, Takao; Ohira, Yoshinobu; Yoshioka, Toshitada; et al.
Abstract The purpose of this study was to investigate a role of heat shock transcription factor 1 (HSF1)‐mediated stress response during regeneration of injured soleus muscle by using HSF1‐null mice. Cardiotoxin (CTX) was injected into the left muscle of male HSF1‐null and wild‐type mice under anesthesia with intraperitoneal injection of pentobarbital sodium. Injection of physiological saline was also performed into the right muscle. Soleus muscles were dissected bilaterally 2 and 4 weeks after the injection. The relative weight and fiber cross‐sectional area in CTX‐injected muscles of HSF1‐null, not of wild‐type, mice were less than controls with injection of physiological saline 4 weeks after the injury, indicating a slower regeneration. Injury‐related increase of Pax7‐positive muscle satellite cells in HSF1‐null mice was inhibited versus wild‐type mice. HSF1‐deficiency generally caused decreases in the basal expression levels of heat shock proteins (HSPs). But the mRNA expression levels of HSP25 and HSP90α in HSF1‐null mice were enhanced in response to CTX‐injection, compared with wild‐type mice. Significant up‐regulations of proinflammatory cytokines, such as interleukin (IL) ‐6, IL‐1β, and tumor necrosis factor mRNAs, with greater magnitude than in wild‐type mice were observed in HSF1‐deficient mouse muscle. HSF1 and/or HSF1‐mediated stress response may play a key role in the regenerating process of injured skeletal muscle. HSF1 deficiency may depress the regenerating process of injured skeletal muscle via the partial depression of increase in Pax7‐positive satellite cells. HSF1‐deficiency‐associated partial depression of skeletal muscle regeneration might also be attributed to up‐regulation of proinflammatory cytokines.